Acute healthcare utilization associated with positive SARS-CoV-2 testing or serology among people experiencing homelessness: A prospective cohort study - Lucie Richard; Brooke Carter; Michael Liu; Rosane Nisenbaum; Stephen W. Hwang (PLoS ONE, 2026)
Background Current literature drastically underestimates SARS-CoV-2 infection among homeless populations, undermining our understanding of acute healthcare utilization following infection. We quantified acute healthcare utilization associated with robustly measured SARS-CoV-2 infection or reinfection among people experiencing homelessness. Methods In this prospective cohort study, we recruited randomly selected individuals experiencing homelessness in Toronto, Canada in summer 2021. Over one year of follow up, participants completed detailed surveys and provided biological samples to test for SARS-CoV-2 infection (RT-PCR and ELISA). Research data were linked to health administrative databases held at ICES, a health administrative data repository. Outcomes were identified using ICD-10 codes and temporal proximity to infection onset, and participants with confirmed infection were compared to participants without infection history. Results Two thirds of participants (n = 640) experienced at least one SARS-CoV-2 infection over the observation period; 25% experienced two or more infections. Prior to Omicron dominating infections, coding identified 1.55 (95% CI 1.0–2.5) hospitalizations and 4.39 (3.9–5.9) emergency department visits per 100 person-years; within 30 days of infection onset, rates were 4.07 (95% CI 2.9–5.6) and 13.69 (95% CI 11.4–16.4), respectively. Hospitalization and emergency department rates were 16.8 and 2.4 times higher than during random 30-day periods without infection. After Omicron variants became dominant, coding identified 2.27 (95% CI 1.1–4.5) hospitalizations and 3.97 (95% CI 2.4–6.7) emergency department visits per 100 person-years; within 30 days of infection, rates were 1.29 (95% CI 0.3–3.3) hospitalizations and 5.8 (95% CI 3.6–9.0) emergency department visits per 100-person years. However, post-Omicron rates within 30 days of infection were not significantly higher than for 30-day periods without infection. Conclusions Despite extremely high SARS-CoV-2 infection and reinfection rates, people experiencing homelessness in Toronto had relatively low rates of acute healthcare utilization following infection. Future work is needed to ascertain rates of chronic outcomes, like post-COVID condition.